Distribution and abundance of Pteroptyx fireflies in Rembau-Linggi Estuary, Peninsular Malaysia. - Wan Jusoh, Wan Faridah Akmal; Hashim, Nor Rasidah; Ibrahim, Zelina Zaiton (Thai Society of Higher Eduction Institutes on Environment, 2010)
Prior to this study, no scientific documentation of firefly distribution and abundance in the Rembau-Linggi estuary, Peninsular Malaysia had been made. Therefore, this study provides important baseline information for the conservation of Pteroptyx spp. and their habitats. Our study was conducted over six months (2008 and 2009) during which we surveyed the distribution and abundance (percentage cover) of congregating fireflies, Pteroptyx spp., in the estuary. We also recorded the plant species on which adult fireflies congregate to mate along the rivers. Our main findings were: 1 Pteroptyx spp. populations occupied the lengths of 0.7 - 9 km of the main rivers in the study area. 2. The percentage of Pteroptyx population size fluctuated over time. 3. The Pteroptyx colonies congregated mainly on four plant species: Sonneratia caseolaris, Rhizophora apiculata, Hibiscus tiliaceus and Ficus sp.